Clinical and Optical Coherence Tomography Angiographic Features in Patients with Postcataract Stenotrophomonas maltophilia Endophthalmitis - Lu Chen; Dahui Ma; Jieting She; Miaohong Chen; Jian Zeng; Jiantao Wang; Guoming Zhang (Journal of Ophthalmology)
Purpose. To report the clinical presentations and optical coherence tomography (OCT) angiographic features of patients with postcataract surgery endophthalmitis due to Stenotrophomonas maltophilia. Methods. A retrospective observational study of 4 patients who developed S. maltophilia endophthalmitis after cataract surgery. Pars plana vitrectomy (PPV) was performed to control the infection. Patients were followed up for six months. Complete ophthalmological examination results were collected before and after PPV. Results. Patients’ response to PPV therapy was excellent and the infection was cured in all cases. OCTA showed that, at the one-month follow-up, the vascular density (VD) and perfusion density (PD) in the superficial capillary plexus (SCP) were significantly lower than those in healthy collateral eyes. As time went on, the SCP-VD and SCP-PD values gradually improved. Conclusions. With early PPV, the infection caused by S. maltophilia can be cured. OCTA provides a quantitative noninvasive assessment to evaluate the severity and prognosis of patients with S. maltophilia endophthalmitis.